2003
DOI: 10.1002/jobm.200390019
|View full text |Cite
|
Sign up to set email alerts
|

Microflora involved in textile dye waste removal

Abstract: Textile dyes are heavily used in factories for coloring different cloth materials. This work was designed to identify microorganisms capable of removing textile dyes, either by biodegradation or by biosorption. We expected to isolate microorganisms adapted to high dye concentrations from sites near textile industry complex. An experiment was conducted to study the efficiency of the isolates in removing textile dyes. The tested dyes were used as carbon and nitrogen sources for isolation of soil and/or water mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 19 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…The Langmuir adsorption isotherm 11,55 assumes that adsorption occurs at specific homogeneous sites within the adsorbents and forms a monolayer on the homogeneous surfaces. The linear form of the Langmuir equation isHere, Q e is the amount of adsorbate adsorbed per unit mass of adsorbent (mg/g), C e is the equilibrium concentration of the adsorbate (mg/L), Q m (mg/g) is the theoretical maximum adsorption capacity, and b (L/mg) is the energy of adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Langmuir adsorption isotherm 11,55 assumes that adsorption occurs at specific homogeneous sites within the adsorbents and forms a monolayer on the homogeneous surfaces. The linear form of the Langmuir equation isHere, Q e is the amount of adsorbate adsorbed per unit mass of adsorbent (mg/g), C e is the equilibrium concentration of the adsorbate (mg/L), Q m (mg/g) is the theoretical maximum adsorption capacity, and b (L/mg) is the energy of adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…10 Biological treatments can be self-sustaining, but are also time-consuming, specific to the type of biotic degradation, and can result in toxic byproducts. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Several actinomycetes have been reported to decolorize reactive dyes, including anthraquinone, phthalocyanine, and azo dyes, through adsorption of the dyes to the cellular biomass (Zhou and Zimmerman, 1993). A few of the actinomycete strains were reported to carry out biodegradation of dyes but with low efficacy (El-Rahim et al 2003).…”
mentioning
confidence: 99%
“…can be good alternatives as they have 40-55% decolorization efficiency. Although there are studies conducted for decolorization of different dyes by Trichoderma species, in literature no similar study on the molasses decolorization with Trichoderma species was found (1,14). In our study, Penicillium species with a molasses decolorization of 44% were detected as the second most successful fungus (Fig.…”
Section: Resultsmentioning
confidence: 99%